Longitudinal evaluation of the structural integrity of teeth affected by molar incisor hypomineralisation - Fragelli, Camila Maria Bullio [UNESP]; Jeremias, Fabiano [UNESP]; Souza, Juliana Feltrin de; Paschoal, Marco Aurélio; Cordeiro, Rita de Cássia Loiola [UNESP]; Santos-Pinto, Lourdes [UNESP] (S. Karger AG, Basel, 2015)
The aim of this prospective cohort study was to evaluate the risk of posteruptive breakdown and the development of caries lesions in teeth with molar incisor hypomineralisation (MIH). A total of 367 permanent incisors and first molars, affected and not affected by MIH lesions, of 45 children with MIH from Araraquara, São Paulo, Brazil, were evaluated at intervals from 6 to 12 months by assessing the severity of MIH, the presence of tooth caries lesions and the treatment needed. During the study period, all patients received preventive care. The data were analysed using Fisher's exact test and actuarial method survival analysis. Significant associations were also found in teeth between the presence of MIH and a DMFT index >0 in all periods and also between the need for treatment and the presence of MIH. The teeth affected by MIH opacities were healthy in 99% of incisors and 93% of molars at the end of the 12-month period. Due to the high likelihood of maintaining the tooth structure in opacities, the complete or premature removal of the affected area is not justified.
Keywords: Child studies; Longitudinal studies; Tooth demineralization